2013
DOI: 10.1002/jgrc.20062
|View full text |Cite
|
Sign up to set email alerts
|

The Congo River plume: Impact of the forcing on the far‐field and near‐field dynamics

Abstract: [1] The first numerical simulations of the Congo River plume dynamics are presented in this study. The different forcing mechanisms responsible for the seasonal variations of the plume extend are separately analyzed and the Regional Ocean Modeling System (ROMS) is employed to carry out both a process orientated study-with simple baseline simulations and a sensitivity study-with realistic 1 year runs setup in 2005. The baseline model is forced only by the river flow, in the presence of realistic bathymetry. Tid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 62 publications
4
43
0
Order By: Relevance
“…2, two centers of salinity variability are found. The southern center is located north of the mouth of the Congo River and has a northwestward extension on the order of 1000 km, comparable to the extension found in the observational study of Hopkins et al (2013) and the modeling study of Denamiel et al (2013). The northern center occupies a somewhat larger area in the Gulf of Guinea., As mentioned above, hereafter we focus our attention on the variability to the south of the Equator, which is more likely to be the direct result of Congo river discharge.…”
Section: Sss Variability As Revealed By Aquariusmentioning
confidence: 79%
See 3 more Smart Citations
“…2, two centers of salinity variability are found. The southern center is located north of the mouth of the Congo River and has a northwestward extension on the order of 1000 km, comparable to the extension found in the observational study of Hopkins et al (2013) and the modeling study of Denamiel et al (2013). The northern center occupies a somewhat larger area in the Gulf of Guinea., As mentioned above, hereafter we focus our attention on the variability to the south of the Equator, which is more likely to be the direct result of Congo river discharge.…”
Section: Sss Variability As Revealed By Aquariusmentioning
confidence: 79%
“…Among the first realistic numerical model simulations of the Congo River plume dynamics, Denamiel et al (2013) also showed that the Congo River plume extends northwestward during most of the year except for the February-March period when the plume has a large westward extension. The northwestward extension of the Congo River plume can be clearly identified in the Aquarius data (Fig.…”
Section: Sss Variability As Revealed By Aquariusmentioning
confidence: 97%
See 2 more Smart Citations
“…Shchepetkin and McWilliams [49] describes an in-depth review of the numerics and formulation. Previous studies have utilised this model in understanding the Congo River plume dynamics [15] and effects on ocean temperature [56]. The model domain extends between 1 o S − 21 o S and 3.7 o E − 13.8 o E with a 10km resolution and 40 terrain-following verti-5 cal levels.…”
Section: Numerical Modelmentioning
confidence: 99%